Effect of Reaction Process Parameters on Photocatalytic CO2 Reduction - Azhari, Mohd Nur Hanif Aiman (IRC, 2016)
Carbon Dioxide (CO2) is one of the most notable greenhouse gasses that contribute to the global warming. CO2 mostly come from fossil fuel as well as other burning activities. For the past decade, huge emission of CO2 is recorded and based on IPCC, the earth’s temperature has been rising roughly 0.6K for the past 100 years. CO2 is a very stable compound and required a significant amount of energy to convert it to useful products. There are lot of carbon-capture technology in the market but the cost of the equipment and also the cost to run is significantly high. Titanium Oxide (TiO2) photocatalyst is the promising semiconductor can be used to convert CO2 into vendible products with a low cost.